Implementasi Good Corporate Governance (GCG) pada PT. Asuransi Askrida Syariah - Ruchiyat, Endang (Banking & Management Review, 2020)
This study aims to determine and describe the extent of the implementation of the principles of Good Corporate Governance at PT. Sharia Askrida Insurance. In addition, this study also aims to find out and describe what factors are obstacles and constraints in implementing the principles of Good Corporate Governance. This research uses a descriptive method with a qualitative approach. The results showed that the implementation of the principles of Good Corporate Governance had been carried out at PT. Asuransi Askrida Syariah, besides that, there are several obstacles in its implementation. Keywords: Good Corporate Governance; Sharia Insurance Company.